PROFIL PRAGMATIK SEBAGAI INSTRUMEN ASESMEN ANAK DENGAN DISORDER BAHASA - Suko Winarsih (Jurnal Bahasa Lingua Scientia, 2010)
As its most general level, the clinical management of children with pragmatic disorders involves two main types of activity, assessment and treatment or intervention. In order to establish which pragmatic skills are impaired, teachers or clinicians must first engage in a process of assessment. The results of assessment provide a basis for the planning of intervention as well as a baseline measurement of the children pragmatic skills. An equally eclectic group of techniques is used in the intervension or treatment of pragmatic disorders. One of them is Pragmatics Profile.